Odnos jezikovnih uporabnikov do splošnih enojezičnih slovarjev - Arhar Holdt, Špela (Slovenščina 2.0, 2018)
The paper presents an international survey on the attitude of language users towards general monolingual dictionaries (GMDs), focusing on the data collected among Slovene participants. The survey was designed within the European Network for e-Lexicography (ENeL) in 2017. The study aims to provide answers to the following research questions: what is the attitude of users towards GMDs as reference books; which language problems do GMDs typically help resolve; and which features of GMDs do users perceive as most important. A questionnaire addressing these topics was translated to the languages of 29 participating European countries and disseminated on national levels. In total, 9,562 questionnaires were collected. In Slovenia, 619 individuals (including both regular as well as non-regular dictionary users) participated in the survey. The results confirmed the pre-existing presumption that in Slovenia (as elsewhere), users typically access dictionaries using a computer. Computer access is also highly preferred compared to both the printed format as well as smartphones and tablets. Secondly, participants often use GMDs to check the appropriateness of language choices (either their own or those made by other language users). GMDs are, however, not perceived as the only and absolute reference when it comes to solving language dilemmas: in case of information gaps, the majority of users turn to alternative options such as Internet browsers. Furthermore, GMDs are typically seen as an exhaustive source of information about Slovene intended for the general public. While the symbolic role of the dictionary (as an authority or a national symbol) is reflected less often in the responses, it is implicitly indicated by the participants' reluctance to relinquish printed dictionaries in spite of the fact that they only use the digital versions. Finally, the participants strongly support public financing of GMD projects. Accordingly, free availability is placed among the top-priority features of GMDs, preceded only by the reliability of their content. The top priorities also include ease of use and up-todate content. In the paper, the detailed presentation of the results is complemented by a discussion on the possible future improvements of the questionnaire. The findings can be used to improve Slovene dictionary resources and to plan further steps of lexicographic user research.
Keywords: dictionary use; dictionary users; general monolingual dictionaries; raba slovarja; slovarski uporabniki; splošni enojezični slovarji; uporabniške raziskave; user research